2014
DOI: 10.1097/mcg.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Treatment Options for Fecal Incontinence

Abstract: Fecal incontinence (FI) is a multifactorial disorder that imposes considerable social and economic burdens. The aim of this article is to provide an overview of current and emerging treatment options for FI. A MEDLINE search was conducted for English-language articles related to FI prevalence, etiology, diagnosis, and treatment published from January 1, 1990 through June 1, 2013. The search was extended to unpublished trials on ClinicalTrials.gov and relevant publications cited in included articles. Conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 114 publications
0
39
0
2
Order By: Relevance
“…Gate Keeper technique uses a dedicate disposable device designed to implant in the inter sphincteric space an hydrophilic material that within 1e2 days after operation increases its thickness while reducing its length; the prosthesis augment the volume of the whole sphincteric complex increasing the continence ability of the muscular system. The placement of the bulking agents in the area limited by the two muscles seems also to reduce dissipation and migration of the prosthetic material, both representing important limits of other Bulking Agents efficacy, especially in the long time period [8,9]. In a study by Ratto et al [10] 14 patients were treated with the Gate Keeper and followed up to 48 months (Median 33.5) after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Gate Keeper technique uses a dedicate disposable device designed to implant in the inter sphincteric space an hydrophilic material that within 1e2 days after operation increases its thickness while reducing its length; the prosthesis augment the volume of the whole sphincteric complex increasing the continence ability of the muscular system. The placement of the bulking agents in the area limited by the two muscles seems also to reduce dissipation and migration of the prosthetic material, both representing important limits of other Bulking Agents efficacy, especially in the long time period [8,9]. In a study by Ratto et al [10] 14 patients were treated with the Gate Keeper and followed up to 48 months (Median 33.5) after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Scoring scales include the Wexner/Cleveland Clinic Florida FI Score, the Vaizey/St. Mark's Incontinence Score, the Fecal Incontinence Severity Index and the Fecal Incontinence Quality of Life scale [5,6].…”
Section: Scoring Scalesmentioning
confidence: 99%
“…Dextranomer microspheres in non-animal stabilized hyaluronic acid (NASHA Dx) is the only Food and Drug Administration (FDA)-approved product for FI 23 . While the implied mechanism of action is to enhance the seal of the anal canal, dextranomer did not significantly increase anal resting or squeeze pressures nor was it superior to biofeedback therapy 24 .…”
Section: Perianal Bulking Injectionmentioning
confidence: 99%
“…The inflated cuff helps to maintain continence, and the deflated cuff facilitates evacuation. Comparisons of its efficacy are confounded by the different scales used to define improvement 23 . The largest single-center study published ( n = 52 patients and 85 devices; mean follow-up, >5 years) showed that full continence is seldom achieved, 14% had device-related infections and 32% required explantation 48 .…”
Section: Artificial Bowel Sphincter (Abs) and Dynamic Graciloplasty Fmentioning
confidence: 99%